Ätiologische Unfalltypen und Empfehlungen für die Prävention im Basketball - Raschka, C.; Glaser, H.; de Marees, H. (Sportverletzung Sportschaden, 1995)
The study is based on 128 basketball accidents. The following accident types were discovered: ankle sprains 54.7%, handling the ball (saving and catching) 15.6%, knee-joint-distorsions 10.2%, collisions, blows and kicks 11.7%, falls 3.9%, spontaneous damage of muscles and tendons 1.6% and getting hurt because of the equipment in the gym 2.3%. Prophylactic precautions might be physiological or synthetic taping, proprioceptor training and preventive sports medical checkups.